Dynamically reversible cross-linked polymer electrolytes with highly ionic conductivity for dendrite-free lithium metal batteries - Wang, Xiaowei (2024)
High-safety PEO-based electrolytes have attracted widespread attention, but their inefficient conduction of Li ions and poor contact with electrode interfaces deteriorate the performances of rechargeable lithium metal batteries. Herein, we design a vitrimer polymer electrolyte (V-SPE-PEG) with abundant dynamic imine bonds via Schiff base reaction between aldehyde and ammonia, which achieves high ionic conductivity and good interfacial compatibility with lithium anode. The dynamic polymer network in V-SPE-PEG exhibits solid-state plasticity because reversible imine bonding reactions enable the integrity of the polymer network to be maintained while altering the cross-linked points under external stimuli. Therefore, this 3D dynamic cross-linked network effectively facilitates the polymer chain dynamics and meanwhile enhances ionic conductivity. Additionally, dynamic bond exchange fosters electrolyte flowability and self-healing during lithium deposition, promoting a tightly integrated electrode/electrolyte interface while inhibiting lithium dendrites growth. Consequently, lithium symmetric cells utilizing the V-SPE-PEG electrolyte demonstrate exceptional long-term cycling stability, surpassing 1100 h and exhibit outstanding ionic conductivity of 2.7 × 10−4 S cm−1 at 30 °C. The LiFePO4||Li battery maintains stable cycling performance at both 40 °C and 60 °C. This study introduces an innovative approach to designing solid-state electrolytes for lithium-metal batteries.